TINGKAT KETAATAN PENGEMUDI SEPEDA MOTOR DALAM PENGGUNAAN LAJUR JALAN PADA BERBAGAI KONDISI ARUS LALULINTAS - Reza Sunggiardi; Leksmono S. Putranto; Robby Ariwibowo (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2007)
Abstract A rapid increase of motorcycle ownership in the last twenty years made a decline to the road safety. This condition led Jakarta government to announce a policy for motorcycles to ride on leftmost lane on the road effectively by January 2007. Therefore, this paper analyzes the obedient of motorcyclist to the policy after about 4 months officially announced in various traffic conditions. This paper analysis is based on the 24 hours observation on both directions of Letjen. S. Parman Arterial Road using video recorder. First of all the distribution of motorcycles across the lanes are analyzed. Furthermore, the percentages of motorcycle in the leftmost lane on different time periods and different V/Cs are compared using t-test. Additionally a Pearson correlation analysis is also conducted between the percentage of motorcycle in the leftmost lane and several other variables. The results shows about 46 percent of motorcyclists obey the policy. The analysis also shows that there are significant differences between the obedience of motorcyclists in the 10.00-16.00 observation periods and in the 22.00-06.00 observation period.Keywords : lane distribution, motorcycle, Jakarta